2018
DOI: 10.1080/20964129.2018.1538665
|View full text |Cite
|
Sign up to set email alerts
|

Priority areas at the frontiers of ecology and energy

Abstract: The complexity of economic development and humanitarian crises means that energy science and technology should be involved in actions that address almost every major challenges of ecosystem health and sustainability. Energy is the engine of the world economy and the key to ecosystems' functioning, which also has a great impact on global warming. The energy crisis, environmental pollution, overuse of natural resources, water supply shortages, global climate disruption, and deteriorating ecosystems are major cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The waste dynamics are provoked by the growth of industrial production and retail turnover; weak development of the waste management and recycling industry, and non-effective legal regulation of waste disposal 7 [19]. 7 Bulletin on current trends in the Russian economy. Ecology and economics: dynamics of air pollution in the country on the In recent years, Russia has seen relatively stable CO 2 emissions.…”
Section: Environmental Constraint Analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The waste dynamics are provoked by the growth of industrial production and retail turnover; weak development of the waste management and recycling industry, and non-effective legal regulation of waste disposal 7 [19]. 7 Bulletin on current trends in the Russian economy. Ecology and economics: dynamics of air pollution in the country on the In recent years, Russia has seen relatively stable CO 2 emissions.…”
Section: Environmental Constraint Analysis Resultsmentioning
confidence: 99%
“…Ключевые слова: экологическая экономика; Россия; рост ВВП; устойчивость; экологические ограничения; сточные воды; отходы производства и потребления; выбросы CO 2 ; уравнение Кайя R. Costanza has developed the meta-paradigm of ecological economics where he has concluded that a sustainable, desirable future is more critical than unsustainable GDP growth [5]. People need to recognize the limitedness of GDP growth by the quality of the environment that is promoted by the followers of the ecological economics direction [5][6][7]. The concept of ecological economics considers a person not as a consumer of natural resources, but as an essential component of an integral ecologicaleconomic system, responsible for understanding his role in the overall global network of the biosphere, in preserving and managing it to achieve sustainability [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Humanity is faced with environmental degradation, new viral outbreaks, and an uncontrollable decline in GDP [Ward et al, 2016]. Nowadays, it is essential not only to maximize profits, but to maintain economic stability and protect bio-diversity [Chou et al, 2018]. The most critical thing is to find a way to maintain balanced socioeconomic development and overcome postepidemic crises [Cao, 2019].…”
Section: Maksim Vasievmentioning
confidence: 99%
“…In 2018 alone, the consumption of freshwater in China reached 0.62 trillion cubic meters, accounting for 77.5% of China's total water resource capacity and about 13% of the world's annual consumption, which is about 127% that of the United States. Among all the water use, agricultural use in 2018 amounted to about 0.38 trillion cubic meters, taking 61.3% of the total annual usage (CEIC 2018;Chou et al 2018).…”
Section: Nature and Resourcesmentioning
confidence: 99%
“…The installed capacity of wind power added to the grid was 20.59 gigawatts in 2018, the year in which the total installed capacity of wind power in China had reached 184 gigawatts, ranking first in the world for nine consecutive years (Dudley 2019). China possesses a solar energy capacity higher than that of any other country in the world, reaching 174 gigawatts by 2018 (Chou et al 2018). Solar power is now cheaper than fossil fuels in hundreds of Chinese cities (Guangfu Network (2018)).…”
Section: Nature and Resourcesmentioning
confidence: 99%